The Absence of STING Ameliorates Non-Alcoholic Fatty Liver Disease and Reforms Gut Bacterial Community - Zhang, Qiang; Chen, Qiongyun; Yan, Changsheng; Niu, Chunyan; Zhou, Jingping; Liu, Jingjing; Song, Yang; Zhou, Fei; Fan, Yanyun; Ren, Jianlin; Xu, Hongzhi; Zhang, Bangzhou (Frontiers in Immunology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is one of the primary causes of cirrhosis and a major risk factor for hepatocellular carcinoma and liver-related death. It has been correlated with changes in the gut microbiota, which promote its development by regulating insulin resistance, bile acid and choline metabolism, and inflammation. Recent studies suggested a controversial role of the stimulator of interferon genes (STING) in the development of NAFLD. Here, we showed that as an immune regulator, STING aggravates the progression of NAFLD in diet-induced mice and correlated it with the changes in hepatic lipid metabolism and gut microbiota diversity. After feeding wild-type (WT) and STING deletion mice with a normal control diet (NCD) or a high-fat diet (HFD), the STING deletion mice showed decreased lipid accumulation and liver inflammation compared with WT mice fed the same diet. In addition, STING specifically produced this hepatoprotective effect by inhibiting the activation of CD8+ T cells. The gut microbiota analysis revealed significant differences in intestinal bacteria between STING deletion mice and WT mice under the same diet and environmental conditions; moreover, differential bacterial genera were associated with altered metabolic phenotypes and involved in related metabolic pathways. Overall, our findings reveal the important regulatory role that STING plays in the progression of NAFLD. In addition, the change in intestinal microbiota diversity may be the contributing factor.